Infants in Early Childhood Education: different trajectories in space (Educação e Pesquisa, 2023)
This paper analyzes how two babies, ages ten to twelve months, explored the space in an infants’ classroom during their entry process in an Early Childhood Education Center in Belo Horizonte, Brazil. While in the field, during the 2017 school year, the following research instruments were used: participant observation, video recordings and fieldnotes. Ethnography in education, in dialogue with cultural-historical psychology and Henri Lefebvre’s production of space theory, enabled us to perceive the baby in a space that is both product and production of such a person. The babies experienced and explored the classroom space during their entry process in the daycare center in different ways: (i) by watching, (ii) walking, (iii) crawling, (iv) touching, (v) fighting for toys, (vi) crying, (vii) learning how to care, (viii) sleeping, (ix) interacting with their peers and other people around them. The babies’ exploration trajectories in this classroom were constituted by the dialectic unity [perception/action], as babies [perceive/act] on the space, the objects, and the people seeking to familiarize themselves with this new space. There was, then, an active search, by the babies, for a recognition of the space and people, so that, perhaps, they could feel belonging to this social environment.